THE EFFECT OF SAFVER PROGRAM ON WINDU SHRIMP FARMERS INCOME - Sasmita Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aim of this research was to determine the ratio of farmer income before and after assistance and to determine the effect SAFVER program (land, fry, feed, and drugs-drugs) on the increase tiger shrimp farmers' income. Sampling method using Simple Random Sampling and analytical methods used are different test score - average and Multiple Linear Regression Analysis. Results of different test average - average based on the value of t - 13:27 count> t - 2:06 table means there is a difference between the farmer’s income before and after SAFVER assistance. Contribution of SAFVER program on the tiger shrimp farmer’s income are based on the value of t - 4:30 count> t - table 2:06 the real impact on tiger shrimp farmers' income. Juveniles, based on the value of t-count -3.68> t - 2:06 table then a real negative effect on the tiger shrimp farmer’s income. Feed, based on the value of t-2:54 count > t - 2:06 table then significantly affect revenues tiger shrimp farmers. Drugs, based on the value of t-hitung 1:00 <t - 2:06 table then not significantly for tiger shrimp farmers income. But from the F test shows that the vast land, fry, feed, and medicine - oabatan significantly affect on the incomes of tiger shrimp farmers.Keywords: safver, tiger shrimp, income